Pengajaran Mubtada' Khabar dengan Pendekatan Kontekstual - Erta Mahyudin; Syifa Yunita Sari (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2020)
Abstract This research is motivated by some problems in Arabic syntactical grammar (nahwu) teaching using conventional learning approaches. The purpose of this study was to describe techniques and procedures of Contextual Teaching and Learning (CTL) approach in teaching nahwu; to reveal students' ability in nahwu learning; and to find out the effect of CTL approach on students' ability. This research used a quantitative research approach with a quasi-experimental type. Data collection technique in this study was: direct observation, interviews and tests. Based on pre-test, it was found that the average score of students is 3.71. The post-test scores showed that the average of students' ability is 7.01. There was an increase in students' abilities after being taught by CTL approach. The value of t-account was 19.02, greater than t-table value at 1% significance level (2.88). The result of t-account also was greater than t-table value at 5% significance level (2.10).